1991
DOI: 10.1063/1.104994
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial CeO2 films as buffer layers for high-temperature superconducting thin films

Abstract: We have prepared epitaxial (100)CeO2 thin films on LaAlO3, sapphire, and yttria-stabilized zirconia using pulsed laser deposition. It is demonstrated in this letter that the CeO2 films are chemically and structurally compatible to the high-temperature superconductor YBa2Cu3O7−δ (YBCO). Epitaxial YBCO films on CeO2/LaAlO3 had a zero resistance temperature and critical current density in a zero field of 90 K and 5.9×106 A/cm2 at 75 K, respectively. Furthermore, epitaxial multilayers of CeO2/YBCO were prepared. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(58 citation statements)
references
References 11 publications
0
57
0
1
Order By: Relevance
“…Finally, it has a lattice parameter that matches significantly closely with that of silicon [5] and high-T c superconducting (HTS) materials. [6] As a matter of fact, CeO 2 represents a considerable challenge to the most commonly used buffer layers for the growth of YBa 2 Cu 3 O 7 thin films on those substrates for which there is highest industrial demand. [7±10] Several techniques have been used to prepare CeO 2 thin films, including magnetron sputtering, [11] electron beam evaporation, [12] pulsed laser deposition, [13] and molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has a lattice parameter that matches significantly closely with that of silicon [5] and high-T c superconducting (HTS) materials. [6] As a matter of fact, CeO 2 represents a considerable challenge to the most commonly used buffer layers for the growth of YBa 2 Cu 3 O 7 thin films on those substrates for which there is highest industrial demand. [7±10] Several techniques have been used to prepare CeO 2 thin films, including magnetron sputtering, [11] electron beam evaporation, [12] pulsed laser deposition, [13] and molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid high microwave losses in such application, it is necessary to grow lms on sapphire substrates, with suitable buer layer to improve matching of the lattice parameters and to prevent chemical reaction between the superconductor and the substrate. It has been found that CeO 2 is the excellent material for the buer between the sapphire and the YBCO [3,4]. It is chemically very stable, it has high melting temperature (2400…”
Section: Introductionmentioning
confidence: 99%
“…While CaF 2 thin films were grown in vacuum, CeO 2 films can be grown in an O 2 background which tends to stabilize the (100) orientation. 1 Even so, we have found that if the growth temperature is too high then (111) lines appear in the x-ray diffraction (XRD) spectra of the CeO 2 film. We also find that attempting to grow YBCO on CeO 2 which has been grown at too high a substrate temperature, results in an insulating, transparent film.…”
Section: Introductionmentioning
confidence: 99%
“…While there is a large lattice mismatch between CeO 2 and the (1102) face of sapphire, (100) CeO 2 can be grown on sapphire under the right conditions. 1,2 In this paper, we report on work towards understanding the growth of CeO 2 thin films.…”
Section: Introductionmentioning
confidence: 99%